PENYULUHAN DAN PRAKTIK PEMBUATAN SABUN CUCI PIRINGCAIR - Suprianto Pasir (Asian Journal of Innovation and Entrepreneurship, 2014)
Lack of knowledge of rural communities to chemicals and processing method hasmade the closing of the business opportunities in the Dusun Sidoharjo, Sidoharjo Village,District Polanharjo, Klaten regency. Therefore, rural communities need training tocultivate the chemical into a product that is safe for the environment. communityempowerment Sidoharjo who mostly work as farmers. So with the manufacture of liquiddish soap extension the public can make its own liquid soap to meet the needs ineveryday life.